Utilization Of Artificial Intelligence In Mobile Applications For Customer Satisfaction At PT. Tirta Mas - Hermanto, Toto; Gulo, Monika (Universitas Utpadaka Swastika, 2025)
The internet has a very positive impact on human life, with the internet people can provide usefulknowledge. In this era of globalization, the development of applications is increasing every year, intechnology in the modern digital era like this, business competition is increasing with the presence ofArtificial Intelligence, a technology that has developed very rapidly in recent years. ArtificialIntelligence has the potential to change various aspects of people's lives ranging from the industrialworld, education to public services. Artificial intelligence is expected to be developed so thatapplications in companies can run well. Artificial intelligence is one of the innovations related to themanufacture of computers and machines that can involve data on a large scale or can be called bigdata, every year the development of artificial intelligence is increasing and has a very positive impacton companies. The data used for one month of research, customer satisfaction data for consumers isused as something significant to solve problems, so researchers provide a form of appreciation for thecompany's sustainability in the future and a form of gratitude. The company continues to develop aproduct, guaranteed quality and attractive services so that consumers can shop again. Based on thequality of service service distance and quality1 is 97% greater than other products, so with thiscustomer satisfaction is the most important.